An updated re-analysis of the mortality risk from nasopharyngeal cancer in the National Cancer Institute formaldehyde worker cohort study. Issue 1 (December 2016) - Marsh, Gary; Morfeld, Peter; Zimmerman, Sarah; Liu, Yimeng; Balmert, Lauren
Abstract Background To determine whether the National Cancer Institute's (NCI) suggestion of a persistent increased mortality risk for nasopharyngeal cancer (NPC) in relation to formaldehyde (FA) exposure is robust with respect to alternative methods of data analysis. Methods NCI provided the cohort data updated through 2004. We computed U.S. and local county rate-based standardized mortality ratios (SMRs) and internal cohort rate-based relative risks (RR) in relation to four formaldehyde exposure metrics (highest peak, average intensity, cumulative, and duration of exposure), using both NCI categories and alternative categorizations. We modeled the plant group-related interaction structure using continuous and categorical forms of each FA exposure metric and evaluated the impact of NCI's decision to exclude non-exposed workers from the baseline category. Results Overall, our results corroborate the findings of our earlier reanalyses of data from the 1994 NCI cohort update. Six of 11 NPC deaths observed in the NCI study occurred in Plant 1, two (including the only additional NPC death) occurred in Plant 3 among workers in the lowest exposure category of highest peak, average intensity and cumulative FA exposure and in the second exposure category of duration of exposure, and the remaining cases occurred individually in three of eight remaining plants. A large, statistically significant, local rate-based NPC SMR of 7.34 (95 % CI = 2.69–15.97) among FA-exposed workers in Plant 1 contrasted with an 18 % deficit in NPC deaths (SMR = 0.82, 95 % CI = .17–2.41) among exposed workers in Plants 2–10. Overall, the new NCI findings led to: (1) reduced SMRs and RRs in the remaining nine study plants in unaffected exposure categories, (2) attenuated exposure-response relations for FA and NPC for all the FA metrics considered and (3) strengthened and expanded evidence that the earlier NCI internal analyses were non-robust and mis-specified as they did not account for a statistically significant interaction structure between plant group (Plant 1 vs. Plants 2–10) and FA exposure. Conclusions Our updated reanalysis provided little or no evidence to support NCI's suggestion of a persistent association between FA exposure and mortality from NPC. NCI's suggestion continues to be driven heavily by anomalous findings in one study plant (Plant 1).